Pulmonary Physiology for Pre-Clinical Students - Binks, Andrew (Open textbook library., 2022)
Pulmonary Physiology for Pre-Clinical Students is an undergraduate medical-level resource for foundational knowledge of pulmonary physiology. This text is designed for a course pre-clinical undergraduate medical curriculum and it is aligned to USMLE(r) (United States Medical Licensing Examination) content guidelines. The text is meant to provide the essential information from these content areas in a concise format that would allow learner preparation to engage in an active classroom. Clinical correlates and additional application of content is intended to be provided in the classroom experience. This resource should be assistive to the learner later in medical school and for exam preparation given the material is presented in a succinct manner, with a focus on high-yield concepts. The 101-page text was created specifically for use by pre-clinical students at Virginia Tech Carilion School of Medicine and was based on faculty experience and peer review to guide development and hone important topics. Instructors reviewing, adopting, or adapting parts or the whole of the text are requested to register their interest at: https://bit.ly/interest-preclinical. Instructors and subject matter experts interested in and sharing their original course materials relevant to pre-clinical education are requested to join the instructor portal at https://www.oercommons.org/groups/pre-clinical-resources/10133. Binks, Andrew., (2022). Pulmonary Physiology for Pre-Clinical Students, Roanoke: Virginia Tech Carilion School of Medicine. https://doi.org/10.21061/pulmonaryphysiology. Licensed with CC BY NC-SA 4.0.